EFFECTIVE USE OF PHYSICAL EDUCATION IN FIGHT AGAINST ADDICTION IN YOUTH (International Journal of Food and Nutritional Sciences, 2022)
The term addiction means – “Being abnormally tolerant to and dependent on something that is psychologically or physical habit-forming”Physical Education refers to the functional capacity of an individual to perform certain kinds of tasks requiring muscular activity. It implies soundness of the body organs. In other words, it reflects the physical fitness of an individual. Physical Education is the quality of whole body in terms of its state of adaptations to physical activity.The addict’s organic cells are fed by way of the drugs so a need of consuming comes afloat. That is to say, the same organism demands for drugs consuming as a way to feed him self. What ever the from of addiction can destroyed the alpha waves or rays which serve to connect the mind with the brain, thus causing severe mental deterioration and leading addiction to madness on other hand, it causes a disorder of the brain neuron that hallucinations are generated. Hallucination is the most noticeable feature of an insane person’s behavior